Attitudes towards menopause and its relationship with sociodemographic factors among postmenopausal women living in a rural area of Jammu: a cross-sectional study - Akhtar, Najma; Bala, Kiran; Gupta, Rajiv K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Positive attitude towards menopause is believed to be associated with positive menopausal experience and vice versa. In order to improve women’s menopausal experience, thereby improving quality of life, it is important to understand their attitude towards menopause. The objectives of the research were to explore the attitude towards menopause and its relationship with various socio-demographic and life style factors among postmenopausal woman in the rural setting. Methods: This community-based cross sectional study was conducted using non probability sampling and house-to-house visit in randomly selected villages falling under rural health block Kot-Bhalwal, Jammu. 245 postmenopausal women were interviewed using modified attitude towards menopause checklist. The data so collected was analyzed using Open Epi version 3.1. For finding statistical significance, unpaired t-test and analysis of variance were used wherever needed. A p value of less than 0.05 was considered statistically significant. Results: The highest percentage of agreement with the positive item was for “a woman gets more confidence in herself after menopause” (77%). The lowest percentage of agreement with the positive item was for “going through menopause really does not change a woman in any important way,” (42.5%). There was a statistically significant mean difference between mean attitude score and religion, and no. of living children (F value=3.14, p value=0.002). No significant association was found between other sociodemographic variables and attitude towards menopause scores. Conclusions: There is a large scope of counseling and health education for improving and enhancing quality of life of postmenopausal women in rural setting of our country.